Paris, Pretoria and the African Continent
XIII, 240 p.
Keywords: France and South Africa, for two generations the premier powers on the African continent, are at a crossroads. With the ending of apartheid and the Cold War, the divisive politics of the recent past are being replaced by a new dynamism of cooperation. Analysing the nature of this complex web of economic and political association is critical to a better understanding of the future direction of this most central of relationships in Africa. Bringing together a host of noted scholars and practitioners in African international relations from both France and South Africa, this book addresses the changing nature of this relationship and its implications for the future of the continent.